Conceptual foundations of the «green» economy - A. A. Nurgissayeva; S. S. Tamenova (Экономика: стратегия и практика, 2020)
The purpose of this research is to analyze the works devoted to the concept of “green” economy, a brief overview of the evolution of the concept, determining the relationship between the concepts of “green” economy, “green” growth and sustainable development. The concept of a “green” economy emerged at the end of the XX century in response to rapidly growing progress in industry and economy, the increase of the world’s population, that led to negative changes in the environment. The scientific community drew the attention of international organizations to the existing problems. As a result, the environment Commission UNEP was established under the auspices of the United Nations, and a definition of the green economy was given in 2009. The “green” economy is a tool for achieving the goals of sustainable development of society, while “green” growth is a strategy for the development of the “green” economy. Based on the literature review and synthesis of various works, general trends in understanding the concept of “green” economy, “green” growth and sustainable development were identified. Differences in the representation of relations between the economy, society and the environment from the point of view of the traditional economy and the “green” economy model are identified. The “green” economy paradigm states that society exists within the environmental limits, so the economy must use reasonable methods of using natural resources and encourage innovation aimed at preserving the environment. Scientific discussions related to the incompatibility of simultaneous development of the “green” economy and economic growth reflect a variety of opinions and approaches to the optimal solution of this issue.